Analisis Tata Letak Fasilitas Toko Dev Bakery & Pizza Menggunakan Metode Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Maulana, Indra; Savira, Silvie; Nadila, Nadila; Wardhana, Dhimas Pradythia Kusuma; Husyairi, Khoirul Aziz (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze and design the facility layout of Dev Bakery & Pizza to improve operational efficiency and space utilization. The research applies the Activity Relationship Chart (ARC) method to identify the level of inter-area relationships and the Total Closeness Rating (TCR) to determine the priority of operational connections between facilities. Based on the result, the dining area and product shelf obtained the highest TCR values, indicating their crucial role as central activity zones that support smooth workflow. An optimized layout design can enhance spatial efficiency, streamline material and labor movement, and strengthen interactions between employees and customers, thereby improving overall operational effectiveness.